Evaluating the Impact of Different Training Methods on SME Business Performance. (February 2013) - Jones, Paul; Beynon, Malcolm J; Pickernell, David; Packham, Gary
With this study we evaluate the impact of different training methods (TMs) on small and medium-enterprises' (SMEs') business performances, utilising a dataset of 3521. We consider the relationship between the satisfaction SMEs have towards their employees' training needs being met by a diverse range of TMs and the levels of impact the training has had on business performance. To investigate both the interdependence and dependence of satisfaction levels of training needs met with business performance, we undertake bivariate correlations and multivariate regression-type analyses (using Regression-type Classification and Ranking Belief Simplex). The results presented offer novel insights into the relationships between TMs and business performance.